(untitled) (EDUCATION IN THE 21ST CENTURY, 2023)
In the current conditions of aggravated socio-economic problems and intensive competitive market the higher education institutions (HEI) are challenged to regularly review their management policies, including Human Resource Management (HRM) practices and strategic HRM approaches to ensure their viability and competitiveness in the sphere of higher education. In order to minimize the negative impact of external factors and to ensure the sustainable efficiency of their activities, HEIs should also review the mechanisms through which they evaluate the effectiveness of their HR performance. This will allow the HEIs to not only identify the urgent problems but also to ensure that they are still functional and competitive. Key Performance Indicators (KPIs) are one of the most effective mechanisms used in HR performance appraisal processes. As an evaluation mechanism, KPIs may serve as a guide to HEIs to improve their HR performance appraisal processes and to clearly visualize to what extent they have succeeded in addressing crucial issues. Based on the above mentioned, the current article elaborates on the essence of KPIs, puts forwards some examples of HR KPIs and proposes some questions through which HEIs can define, re-develop and improve their HR KPIs as well as reform the evaluation of HR performance.